2014
DOI: 10.1542/peds.2013-2404
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nebulized Beclomethasone in Preventing Viral Wheezing: An RCT

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Viral wheezing is common in preschool-aged children. The efficacy of inhaled steroids in preventing viral wheezing is debated. Despite this debate, nebulized beclomethasone is widely prescribed (particularly in a few countries) to children with upper respiratory tract infections. WHAT THIS STUDY ADDS:Findings from this study confirm that inhaled steroids are not effective in preventing viral wheezing. Moreover, no differences were found in the persistence of symptoms (eg, runny no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In terms of ED/doctor visits, only one study reported this outcome and shows an effect favoring ICS (RR = −0.70 [0.50 to 0.97]); in terms of hospital admissions, the effect of ICS was not significant different compared with placebo. However, a recently published parallel RCT [13] comparing intermittent beclomethasone by nebulizer (400 μg twice daily) vs. placebo for 10 days in 525 Italian preschoolers with mild EVW (had at least 1 episode of viral wheezing diagnosed by a physician in the preceding 12 months, and had no or minimal asthma-like symptoms between distinct airway infections) showed no group difference in % of wheezing diagnosed by the pediatrician during a upper respiratory tract infection episode (primary outcome) nor reducing severity of wheezing, asthma-like symptoms score, extra visits, ED attendance, prescription of rescue drugs.
Fig. 2Pooled RRs (with 95 % CI) for exacerbation requiring oral steroids of eligible studies comparing episodic ICS vs placebo in infants or preschoolers [12].
…”
Section: Resultsmentioning
confidence: 99%
“…In terms of ED/doctor visits, only one study reported this outcome and shows an effect favoring ICS (RR = −0.70 [0.50 to 0.97]); in terms of hospital admissions, the effect of ICS was not significant different compared with placebo. However, a recently published parallel RCT [13] comparing intermittent beclomethasone by nebulizer (400 μg twice daily) vs. placebo for 10 days in 525 Italian preschoolers with mild EVW (had at least 1 episode of viral wheezing diagnosed by a physician in the preceding 12 months, and had no or minimal asthma-like symptoms between distinct airway infections) showed no group difference in % of wheezing diagnosed by the pediatrician during a upper respiratory tract infection episode (primary outcome) nor reducing severity of wheezing, asthma-like symptoms score, extra visits, ED attendance, prescription of rescue drugs.
Fig. 2Pooled RRs (with 95 % CI) for exacerbation requiring oral steroids of eligible studies comparing episodic ICS vs placebo in infants or preschoolers [12].
…”
Section: Resultsmentioning
confidence: 99%
“…The AAP 2006 guideline reports that neither bronchodilators nor corticosteroids have significant efficacy in the treatment of bronchiolitis, which is supported by the current literature (Clavenna et al, 2014;Gadomski & Scribani, 2014). One prior study conducted in 2004, before the publication of the AAP 2006 guideline, demonstrated a synergistic effect of nebulized bronchodilators and systemic corticosteroids when used concurrently (Kuyucu, Unal, & Yilgor, 2004).…”
mentioning
confidence: 83%
“…Our daily experience suggests that many wheezy children are treated with pre-emptive ICS, but at lower doses than have been proven to be effective 52. In practice, we suggest that the fluticasone dose should not exceed the licensed dose of 150 μg twice a day by a metered-dose inhaler and a spacer, given the number and duration of viral colds in normal preschool children and the risk of side effects including growth suppression and adrenal failure with higher doses.…”
Section: On the Edge Of Reasonmentioning
confidence: 99%